Masculinities and sexualities of sugar cane cutters in the town of Candelaria, Valle - Castaño López, Jairo Alexander (Sociedad y Economía, 2011)
The analysis of family life, the educational, sexual, and emotional biographies and experiences of sexuality in the light of differences that arise in the experiences of workers through sociological factors such as sex/gender, social class, place of origin, skin color and age of cane cutters when they were in the stages of childhood, adolescence and adulthood, allows us to observe the processes of construction of masculinity. The results of the interviews show the ways in which hegemonic masculinity is expressed in the experience of workers and the various “alternative” masculinities that are built on this model and that interact with other figures in different spheres.